Effect of ozone microbubbles and ultrasonic irradiation on pesticide detoxification in tangerine cv. Sai Nam Pung - K. Whangchai (2018)
© All Rights Reserved. Ethion is an organophosphate pesticide which is widely used in tangerine cultivation. This research was conducted as an investigation on the efficiency of ozone microbubbles and ultrasonic irradiation in combination (OMB/US) on ethion residue reduction in tangerine cv. Sai Nam Pung. Ethion standard (10 ppm) treated with OMB/US was compared with individual ozone microbubbles (OMB) and ultrasonic frequency1000 kHz (US) at various time intervals (15, 30, 45, and 60 min). It was observed that the ethion concentration of treated samples had significantly decreased in direct proportion to the reaction time, as compared with the control. The analysis was carried out to find out which OMB/US treatment showed lower case heading/subheading the most effectiveness on ethion degradation over OMB or US alone. The rate constant (k) of OMB/US was revealed as 0.79 × 10 -2 min -1 , which is the maximum value obtained of all the treatments. The detoxification levels of OMB/US, OMB, and US were determined using the brine shrimp lethality test method. OMB/US showed the maximum level of LC 50 , at 281.43 mgL -1 , when compared the control which have LC 50 at 5.41 mgL -1 , the ethion residue on tangerine fruit was treated by OMB/US, the same as the previous method. The results showed that the percentage of ethion degradation had increased, which was in addition to the rise in the reaction time. OMB/US showed the highest rate of reduction as occurring within 15 min. It was observed that ethion had reduced by 73% after OMB/US treatment for 60 min reaction time. Thereafter, tangerine fruits were stored at 5°C for 35 days to determine quality changes. The peel color change, percentage of weight loss, TSS, TA, and ascorbic acid content after all the treatments were found to be not affected by OMB/US.